A NEW PRENYLATED FLAVANONE FROM THE ARIAL PART OF Orthosiphon stamineus - M. Amzad Hossain; Atiqur Rahman; Sun Chul Kang (Indonesian Journal of Chemistry, 2008)
Phytochemical investigations on the chloroform extract of the arial part of Orthosiphon stamineus resulted in isolation of one new prenylated compound 5,7-dimethoxy-3,4′-dihydroxy-3′,8-di-C-prenylflavanone together with four known flavonoids compounds, sinensetin, eupatorin, 5,6,7,4¢-tetramethoxyflavone and 3-hydroxy-5,6,7,4¢-tetramethoxyflavone. The structures were deduced on basis of different analytical methods such as UV, IR, 1H-NMR, 13C-NMR, DEPT, COSY, HMBQ and GC-MS. The prenylated compound is reported for the first time from this plant.